EXPLORING ALTERNATIVES FOR VISUAL WORD GRAMMATICAL PRIMING PROCEDURE: AN ERP STUDY - Ković, Vanja; Sovilj †, Platon; Lalović, Dejan (Primenjena psihologija, 2018)
In search of the optimal method for assessing grammatical context effects on the visual word processing, we designed a study to demonstrate that in a simple task of reacting to “oddball“ word pairs, subjects read and linguistically processed both the function and the content word simultaneously presented in a given pair. Properties of the oddball ERP paradigm allowed for stipulation that word pairs would evoke P300 potentials, and that properties and differences between potentials evoked by grammatically congruent and grammatically neutral pairs would indicate a type of stimuli processing. To test such prediction, we paired a noun and a verb with a congruent preposition and a personal pronoun respectively, preceding them to create a grammatically constrained condition, or with the conjunction preceding both target words to create unconstrained condition. The stimuli were employed in the two-stimulus oddball paradigm. Main outcome of our experiment was that the stimuli chosen evoked clear P300 potential as deviants in three out of four situations. More interestingly, in each of the situations P300 peaked well after 400 ms, falling near the upper limit of P300 range as usually reported. Such P300 latencies marked semantic processing (Polich, 2007), and indicated subjects read and linguistically processed both words in pairs. Our results suggested that in order to study effects of the grammatical context on the visual word processing, the standard priming procedure in which primes temporally preceded targets might not be required, or that it could at least be complemented by methods involving simultaneous primes and target presentation less burdened by technical issues.